Significance of Persistent Inflammation in Respiratory Disorders Induced by Nanoparticles - Yasuo Morimoto; Hiroto Izumi; Etsushi Kuroda (Journal of Immunology Research)
Pulmonary inflammation, especially persistent inflammation, has been found to play a key role in respiratory disorders induced by nanoparticles in animal models. In inhalation studies and instillation studies of nanomaterials, persistent inflammation is composed of neutrophils and alveolar macrophages, and its pathogenesis is related to chemokines such as the cytokine-induced neutrophil chemoattractant (CINC) family and macrophage inflammatory protein-1α and oxidant stress-related genes such as heme oxygenase-1 (HO-1). DNA damages occur chemically or physically by nanomaterials. Chemical and physical damage are associated with point mutation by free radicals and double strand brake, respectively. The failure of DNA repair and accumulation of mutations might occur when inflammation is prolonged, and finally normal cells could become malignant. These free radicals can not only damage cells but also induce signaling molecules containing immunoreaction. Nanoparticles and asbestos also induce the production of free radicals. In allergic responses, nanoparticles act as Th2 adjuvants to activate Th2 immune responses such as activation of eosinophil and induction of IgE. Taken together, the presence of persistent inflammation may contribute to the pathogenesis of a variety of diseases induced by nanomaterials.